2013
DOI: 10.4161/cam.22479
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition and biomechanical properties of in vivo-derived basement membranes

Abstract: Basement membranes (BMs) evolved together with the first metazoan species approximately 500 million years ago. Main functions of BMs are stabilizing epithelial cell layers and connecting different types of tissues to functional, multicellular organisms. Mutations of BM proteins from worms to humans are either embryonic lethal or result in severe diseases, including muscular dystrophy, blindness, deafness, kidney defects, cardio-vascular abnormalities or retinal and cortical malformations. In vivo-derived BMs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 62 publications
(69 reference statements)
3
82
0
9
Order By: Relevance
“…Previous AFM studies showed that the mechanical strength is in the mPa range, very similar to the articular cartilage and about 1000-fold stronger than cell layers. 18,24,25 Our results underline previous reports 20 describing that the average stiffness of the ILM is over fivefold higher at the retinal side as compared with the vitreal side. This difference nicely explains the fact that the ILM curls up towards its vitreal side after peeling.…”
Section: Discussionsupporting
confidence: 81%
“…Previous AFM studies showed that the mechanical strength is in the mPa range, very similar to the articular cartilage and about 1000-fold stronger than cell layers. 18,24,25 Our results underline previous reports 20 describing that the average stiffness of the ILM is over fivefold higher at the retinal side as compared with the vitreal side. This difference nicely explains the fact that the ILM curls up towards its vitreal side after peeling.…”
Section: Discussionsupporting
confidence: 81%
“…The BM subtending the retina (which has a similar laminin-rich composition) has a modulus between 1 and 4 MPa, with a difference in matrix biomechanics between its two faces [38], suggesting that despite the thinness of this structure it specializes into sides.…”
Section: The Basement Membrane In the Normal Breast Is A Tumor Supprementioning
confidence: 99%
“…Breast cancer is not a single disease [38]: breast cancer prognosis varies with expression of key hormone receptors: estrogen receptor (ER), progesterone receptor (PR) and her2/neu/ ERbB2 (Her2) [56] histologic grade [57], and presence of metastasis. Recent evidence suggests that the microenvironment in these tumors is different [58,59].…”
Section: Breast Cancer Subtypesmentioning
confidence: 99%
“…Previously, it was shown that various basement membranes containing a full arsenal of ECM molecules enhance neurite outgrowth in vitro [73,74] and axonal extension in the lesioned adult brain [74] . Basement membrane is a specific type of ECM secreted by support cells and composed of >20 different molecules [75] . They are of specific interest for axon regeneration due to their crucial role in regeneration in the damaged peripheral nerve [76] .…”
Section: Polymersmentioning
confidence: 99%
“…Basement membrane is a specific type of ECM secreted by support cells and composed of >20 different molecules [75] . They are of specific interest for axon regeneration due to their crucial role in regeneration in the damaged peripheral nerve [76] .Although it is typically difficult to isolate and manipulate these fragile substrates without causing damage, recent advances have made successful isolation of various basement membranes possible [75] . Several combination ECM materials isolated from mammalian sources are commercially available [52,77] , while others are in various stages of development and characterization [19,[78][79][80] .…”
mentioning
confidence: 99%